2019
DOI: 10.9755/ejfa.2019.v31.i3.1920
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical and Physiological Characters of Kaffir Lime (Citrus hystrixDC) Seedling under Artificial Shading and Pruning

Abstract: Kaffir lime (Citrus hystrix DC) is a minor citrus and its leaves are locally used for spices and essential oils. This study aimed to evaluate agronomical and physiological characters of kaffir lime seedling under modified cultural practices in order to improve leaf production. Shading and pruning were applied on five-month-old seedling during the rainy season, November 2017 to March 2018 in Bogor, Indonesia. The results showed that shading significantly improved the plant growth by 84%, and leaf number by 37%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…The heat stress on potatoes was reported to reduce the leaf size 29 and leaf area 30 , form a thinner petiole 31 and then constrain potato production 32 . Leaf chlorophyll content was reported to be an important variable since this result related to the rate of plant photosynthetic rate 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The heat stress on potatoes was reported to reduce the leaf size 29 and leaf area 30 , form a thinner petiole 31 and then constrain potato production 32 . Leaf chlorophyll content was reported to be an important variable since this result related to the rate of plant photosynthetic rate 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Many scientists used leaf measurement in various studies of ecology, plant stress, plant-environment interaction, and precision agriculture (Sestak et al 1971;Kinhal 2019). In earlier reports, both leaf variables also good proxies of plant growth (Salazar et al 2018) and plant physiological condition (Bleasdale 1984) in response to various stressing condition, such as pruning (Palliotti and Poni 2011;Budiarto et al 2018), grafting (Blanco and Folegatti 2005), shading (Budiarto et al 2019b), interspecific plant competition (Harper 1977), elevated CO2 (Ewert 2004), drought (Shekafandeh and Hojati 2012;Adamipour et al 2016;Dadashpour et al 2017), and salinity (Qrunfleh et al 2017). Leaf area is frequently used to monitor the biomass accumulation (Potter and Jones 1977;Weraduwage et al 2015), leaf expansion, and also net assimilation rate (Lakitan et al 2017), while leaf weight is used to measure relative growth rate, leaf harvesting index (Salazar et al 2018), and biomass accumulation (Tieszen 1982).…”
Section: Introductionmentioning
confidence: 90%
“…The present study found that the GA3 at 400 and 600 ppm produced a significantly higher plant than paclobutrazoltreated plants. Paclobutrazol also diverted photosynthates into the root system, leading to the limitation of canopy growth and plant height (Bridgemohan and Bridgemohan 2014), similar to the root pruning effect (Budiarto et al 2019a), but opposite to the canopy pruning effect (Budiarto et al 2019b).…”
Section: Plant Heightmentioning
confidence: 99%
“…Leaf was an important variable to be an appropriate proxy of plant growth (Salazar et al 2018;Hamdani et al 2022), morphological feature (Efendi and Budiarto 2022;Budiarto et al 2021a;2021b;Djarot et al 2021), phytochemical content (Efendi et al 2021), and physiological condition (Budiarto et al 2018;Budiarto et al 2019b). Leaf size, in terms of leaf length and width, of sweet corn at present proved to be significantly affected by the application of PGR.In theory, the application of GA3 was able to increase leaf length by increasing plant cell division and elongation, but higher doses of gibberellic acid inhibited leaf growth yielding shorter leaves (De Souza and MacAdam 2001; Utami et al 2018).…”
Section: Leaf Length and Widthmentioning
confidence: 99%